THE STATE OF ANXIETY, DEPRESSION, AND STRESS IN HOSPITALIZED PATIENTS WITH CONFIRMED COVID-19 INFECTION - MITRA, SUBHASIS; MITRA, DALIA; DUTTA, ABHIJIT (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: In the past few months, the COVID-19 pandemic has drastically invaded the globe with its high infectivity. In this situation, people’s mental health is of utmost importance but poorly reported, especially in patients. We conducted this cross-sectional study among laboratory-confirmed hospitalized patients to evaluate the burden of depression, anxiety, and stress symptoms. Methods: We used depression, anxiety and stress scale 21 (DASS-21) to evaluate respective mental health components. A total of 114 hospitalized patients participated in this study. Of which, 65.79% were male patients. Results: The reported depression, anxiety, and stress were 77.2%, 84.2%, and 54.4%, respectively. An inverse relationship of the total DASS-21 score was found with the age of the participants. Conclusion: Such a high prevalence of mental health outcome suggests the need for further evaluation and addressing the problem with immediate concern.